2015
DOI: 10.1161/strokeaha.114.007213
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the Stroke Relevant HDAC9 Gene Attenuates Atherosclerosis in Accord With Allele-Specific Effects at 7p21.1

Abstract: ApoE−/− mice exhibited markedly reduced lesion sizes throughout atherosclerotic aortas and significantly less advanced lesions. The proportion of Mac3-positive macrophages was higher in plaques from HDAC9 −/− ApoE −/− mice, but this was largely because of a lower proportion of advanced lesions. Analysis of human atherosclerotic plaques revealed no association between rs2107595 and specific plaque characteristics. Conclusions-Our results suggest that HDAC9 represents the disease-relevant gene at the stroke and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…The variant rs2107595 resides in regulatory DNA, and the risk allele of this variant has previously been shown to associate with elevated expression levels of HDAC9 (27). Genetic ablation of HDAC9 attenuates atheroprogression in atherosclerosis-prone mice (27,28). Hence, the effects of this locus seem to be mediated by altered HDAC9 expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variant rs2107595 resides in regulatory DNA, and the risk allele of this variant has previously been shown to associate with elevated expression levels of HDAC9 (27). Genetic ablation of HDAC9 attenuates atheroprogression in atherosclerosis-prone mice (27,28). Hence, the effects of this locus seem to be mediated by altered HDAC9 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…The variant rs2023938, which reached exome-wide significance in the current study, is located in the 3′-UTR of HDAC9 and is in high LD with rs2107595 and other variants previously shown to be associated with LAS (4,11). The variant rs2107595 resides in regulatory DNA, and the risk allele of this variant has previously been shown to associate with elevated expression levels of HDAC9 (27). Genetic ablation of HDAC9 attenuates atheroprogression in atherosclerosis-prone mice (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…From METASTROKE , we can learn the polymorphism loci rs2107595 resides in the intergenic areas between HDAC9 and TWIST1 gene. Azghandi et al (2015) carried out a gene expression study in peripheral blood mononuclear cells, and the results indicated that rs2107595 only regulated the mRNA level of HDAC9 but not of TWIST1/FERD3L. Hence, rs2107595 is considered more likely in HDAC9 gene.…”
Section: Introductionmentioning
confidence: 99%
“…43 More importantly, overexpression of macrophage HDAC9 markedly decreases the expression of ATP binding cassette (ABC) transporters, such as ABCA1 and ABCG1, which, in turn, inhibits cholesterol efflux from macrophages. 44 Macrophage-derived LPL and its associated lipolysis product were shown to decrease expression of ABCA1 and ABCG1, resulting in reduced cholesterol efflux from cells.…”
Section: Effects Of Mir-182 On Proinflammatory Cytokines and Lipids Imentioning
confidence: 99%